2020
DOI: 10.1108/ebr-09-2019-0202
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of FDI by Indian and Chinese MNEs in Europe

Abstract: Purpose Exploration of potential markets in foreign regions such as Europe becomes critical for emerging market multinational enterprises (MNEs). This study aims to investigate structural factors that affect the location choice of Chinese and Indian MNEs in Europe and compares them with USA and Japanese MNEs. Design/methodology/approach The authors use a holistic approach to identify possible configurations of the determinants of Indian and Chinese outward foreign direct investment (FDI) into 38 European cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…An Indian study revealed that to increase FDI inflow and export development, Indian officials have focused more on expanding all types of logistical infrastructure [18]. Affirming the above-explained findings, Avioutskii and Tensaout [19] examined the importance of logistics infrastructure in attracting FDI into the European region in a similar study. Similarly, Souza, Goh [20], highlighted that multinational firms are one of the many parties involved in FDI, contributing significantly to global FDI flows.…”
Section: Literature Reviewmentioning
confidence: 82%
“…An Indian study revealed that to increase FDI inflow and export development, Indian officials have focused more on expanding all types of logistical infrastructure [18]. Affirming the above-explained findings, Avioutskii and Tensaout [19] examined the importance of logistics infrastructure in attracting FDI into the European region in a similar study. Similarly, Souza, Goh [20], highlighted that multinational firms are one of the many parties involved in FDI, contributing significantly to global FDI flows.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Foreign direct investment has been questioned due to reducing employment in the home country, as well as increasing employment, promoting technology transfer, and encouraging growth and exports in the host country. Foreign direct investment (FDI) through increased capital inflows leads to more employment, more innovation, and development of national industry and higher exports, which in turn improves national competitiveness (Owczarczuk, 2020;Avioutskii & Tensaout, 2020). Furthermore, based on some empirical literature, the impact of foreign direct investment on national competitiveness and entrepreneurship depends on the level of development of the countries (Rusu & Roman, 2018).…”
Section: Foreign Direct Investment (Fdi)mentioning
confidence: 99%
“…EMNEs are no exception. Well-established institutions attract EMNEs to take advantage of such favorable conditions and reduce transaction costs for foreign operations (Avioutskii & Tensaout, 2021;Cui et al, 2016). They also help boost risk-taking capabilities by reducing information asymmetry and the regulatory ambiguity associated with OFDI activities (Lu et al, 2014).…”
Section: The Role Of Host Country Institutionsmentioning
confidence: 99%